2020
DOI: 10.1177/1069072720976376
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Career Goal Discrepancy Scale: Development and Initial Validation

Abstract: The 15-item Positive Career Goal Discrepancy Scale was developed to assess emerging adults’ appraisals of the extent to which their current career progress exceeds their set career goals. We generated 32 items based on a literature review, focus groups, and expert reviews, used EFA ( N = 244, M age 18.7 years; 65% women) to reduce the number of items, and CFA ( N = 254, M age 18.7 years; 68% women) to confirm the factor structure and demonstrate superior reliability at the total score level (ω reliability = .9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 57 publications
(121 reference statements)
2
12
0
Order By: Relevance
“…Students can consider adjusting the process of goal striving or a re-assessment of their goals so their motivation and effort can be better maintained. For instance, it might be useful to show those who are feeling overwhelmed by the effort they put forth in their goals that they are doing more than enough (Akmal et al, 2020). Last, this study demonstrated that the scores from GSS were positively associated with students’ mindset and psychological health, which is of great concern to educational practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Students can consider adjusting the process of goal striving or a re-assessment of their goals so their motivation and effort can be better maintained. For instance, it might be useful to show those who are feeling overwhelmed by the effort they put forth in their goals that they are doing more than enough (Akmal et al, 2020). Last, this study demonstrated that the scores from GSS were positively associated with students’ mindset and psychological health, which is of great concern to educational practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Positive career goal discrepancies. The 15-item Positive Career Goal Discrepancy Scale (Akmal et al, 2021) assesses the extent to which participants appraise their current career progress as exceeding their anticipated progress. The scale taps three broad areas of ability/achievement (e.g., "What I have achieved to date in my career has exceeded my parent's expectations"), standard ("I have higher career goals for myself than my parents have for me"), and effort discrepancy ("I am putting more effort into achieving my career goals than I did in the past").…”
Section: Methodsmentioning
confidence: 99%
“…Progress is appraised against internal (e.g., past performance and personal goals) and external comparators (e.g., peer and family expectations; Bandura, 1991;Carver & Scheier, 1990). Akmal et al, (2021) identified three positive career goal discrepancy domains: achievement/ability, standard, and effort discrepancy. Positive achievement/ability discrepancies result when individuals appraise their current abilities achievements, and skills as more than needed to achieve the set career goal.…”
Section: Positive Career Goal Discrepanciesmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Appropriate counseling regarding professions by parents also has an effective role since the advisers have to fulfill the choice of a career regarding the individual’s skills and interests. 11 …”
Section: Introductionmentioning
confidence: 99%